Preparation and Properties of Photochromic Blue Microcapsules (Journal of Fiber Bioengineering and Informatics, 2018)
In this paper photochromic microcapsules were prepared by in-situ polymerization using melamineformaldehyde resin as wall materials and tetrachloroethylene solution with photochromic materials ascore materials. In order to attain a suitable particle size of microcapsules to be used in fabric byblending or coating, high emulsifiers were used to produce smaller oil drop. The factors affecting theproperties of microcapsules were discussed in detail, such as emulsification time, PVA concentration andacidification time. The experiments revealed that the average particle size of microcapsules increasedfirstly then decreased with the increase of emulsification time. The same trend was observed whendifferent concentrations of emulsifiers were used. Acid conditions directly affected the airproof andtransparency of microcapsules. Finally, the optimum process condition was determined. The resultsshowed that the particle size of microcapsules ranged from 1 μm to 20 μm and the photochromic bluemicrocapsules prepared at the optimum process condition could carry the color change quickly andreversibly. The knit fabric with photochromic property was obtained by coating with photochromic bluemicrocapsules, and the fabric thus formed could change its color quickly and as well as be reversed backto its original color for many times. The knit fabric had good washing fastness and rubbing fastness.Therefore photochromic blue microcapsules showed signs of potential application in the textile field.